MOCVD of Cobalt Oxide Using Co-Actylacetonate As Precursor: Thin Film Deposition and Study of Physical Properties - S.M. Jogade; P.S. Joshi; B.N. Jamadar; D.S. Sutrave (Журнал нано- та електронної фізики)
Metal Organic Chemical Vapor Deposition (MOCVD) is the deposition method of choice for achieving conformal uniform (composition and thickness) continuous thin films over the micron geometry topology necessary for implementing advanced devices. Thin films of cobalt oxide were prepared by MOCVD technique on alumina substrate using a cobalt acetylacetonate as precursor. The thin films of cobalt oxide were deposited on alumina substrate by MOCVD at four different temperatures viz 490 °C, 515 °C, 535 °C, 565 °C. The as deposited samples are uniform and well adherent to the substrate. Thickness of the cobalt oxide film is maximum at temperature 535 °C. The crystalline and phase composition of films were examined by X-ray diffraction. The XRD reveals the crystalline nature with cubic in structure for all the samples. The surface morphology of the films were studied by scanning electron microscopy. The SEM image shows well defined closely packed grains for all the samples. The hexagonal shape of grains are observed for sample at temperature 515 °C. Raman spectroscopy shows Fm3m, 225 space groups for cobalt oxide thin films deposited on alumina substrate.